External assessment of teachers’ roles during children’s free play and its relation to types of children’s play - Rüdisüli, Cornelia; Duss, Isabelle; Lannen, Patricia; Wustmann Seiler, Corina (Frontiers in Education, 2023)
Teachers in early childhood education and care (ECEC) assume various roles in children's free play, such as tutor, classroom manager, co-player, and director. Recent research has shown that teacherrelated characteristics such as work experience and classroom-related characteristics such as children's age are significant predictors of teachers' roles. However, these roles have mostly been assessed through self-report rather than external observation using standardized scales. Furthermore, it is unclear how teachers' roles depend on the types of children's play, such as construction play and dramatic play. To address these research gaps, we observed 80 teachers during 291 observation cycles in childcare centers and kindergartens in Switzerland. We developed a standardized observation scale to simultaneously assess both teachers' roles during children's free play and the types of children's play. Additional teacher-and classroom-related predictors were assessed with an online questionnaire for teachers. The results of a multilevel regression analysis showed that the roles observed differed in the type of play in which children engaged. However, teacher-and classroomrelated predictors were more relevant and explained more variance in teachers' roles than the types of children's play. The findings may stimulate self-reflection by ECEC teachers on the roles they assume during children's free play.